THE TYPES OF POLITENESS STRATEGY IN “17 AGAIN” MOVIE SCRIPT: PRAGMATIC APPROACH - Safitri, Vira; Ambalegin, Ambalegin (Universitas Putera Batam, 2022)
Politeness strategy is a language phenomenon that is based on the form and purpose of each. Strategy is needed to deliver communication with meaning and purpose to be conveyed and interpreted properly. This study aimed to identify and analyze the politeness strategy used in the “17 Again” movie script. This study used a qualitative descriptive approach in research. The movie script of “17 Again” is used as a data source in this research. This research used Brown and Levinson theory about the types of politeness strategies. The results of the study found that there were 15 data politeness strategies found in the movie script, which were divided into: positive politeness (4), negative politeness (2), bald-on record (6), and off record (3). This research has significances which are theoretically and practically. This research theoretically is expected to contribute about future research in pragmatics especially for the types of politeness strategy. Practically this research is expected to be a comparison and support for future researchers.